Factors Affecting Psychological Adaptation of Primiparous Postpartum Mothers - Riana Sari; Yulia Irvani Dewi; Veny Elita (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2022)
The role of a mother for the first time is a pressure and stressor for primiparous mothers during the postpartum period, psychological adaptation is needed at this time. This study aims to determine the factors that influence the psychological adaptation of primiparous postpartum mothers in the work area of ??Payung Sekaki Health Center. This study used a descriptive correlational design and a cross sectional approach. The research sample was 50 respondents who were taken based on the inclusion criteria using accidental sampling technique. The analysis used is univariate analysis and bivariate analysis using chi square test. There is a relationship between husband's social support and history of childbirth on psychological adaptation of primiparous postpartum mothers with p value (0.033) < ? (0.05). There is no relationship between family economic status and maternal psychological adaptation primiparous postpartum with p values (0.231) > ? (0.05) and there is no relationship between culture and psychological adaptation of primiparous postpartum mothers with p value (0.944) ? > (0.05). Based on the results of the study, it can be concluded that husband's social support and history of childbirth affect adaptation psychological primiparous postpartum mothers. Meanwhile, family economic status and culture do not affect the psychological adaptation of primiparous postpartum mothers. It is suggested to the health care to be able to provide postnatal class facilities for mothers to minimize psychological adaptation disorders for postpartum mothers.